EXPLORING EFL LEARNERS’ READING COMPREHENSION THROUGH PQRST - Ni Putu Ema Ayu Linda; I Ketut Wardana; Ni Luh Putu Dian Sawitri (Journal on Studies in English Language Teaching (JOSELT), 2022)
This study examines how reading comprehension can be enhanced through an intervention of PQRST. This study used a classroom action research design by monitoring and controlling the teaching-learning process. The subjects of the study were 30 eighth-grade students of SMP Negeri 3 Tampaksiring. The data were collected through tests and questionnaires after the instruction of PQRST in 2 cycles. The study revealed that the student’s comprehension of the contents of English text gradually increased as can be seen from the comparison of the pre-test which was 52.33 categorized as “insufficient” and the mean score post-test 1 was 79.56 categorized as “good”, and the mean score of post-test II was 88.36 categorized as “excellent” achievement. The result of the post-test in each cycle clearly showed that there was significant improvement concerning the subjects’ ability in reading comprehension. Besides, the subjects also gave positive responses to the implementation of PQRST technique in teaching reading comprehension. Therefore, through this technique, the EFL teachers can allocate the students’ difficulties, stimulate students’ knowledge, and provoke students’ positive learning behavior.